ABUNDANCE AND VERTICAL DISTRIBUTION OF THE CHAETOGNATH PARASAGITTA ELEGANS (VERRILL) UNDER THE SEA ICE IN SAROMA KO, A LAGOON ON HOKKAIDO, JAPAN (Ninth Symposium on Polar Biology) - コトリ, モリユキ; ニシヤマ, ツネオ; タニムラ, アツシ; ワタナベ, ケンタロウ; KOTORI, Moriyuki; NISHIYAMA, Tsuneo; TANIMURA, Atsushi; WATANABE, Kentaro (National Institute of Polar Research, 1987)
P(論文) Abundance, vertical distribution and maturity of the chaetognath Parasagitta elegans under the sea ice in a shallow lagoon (the depth of bottom, <20m) on Hokkaido in the daytime in February 1986, were examined. The abundance was estimated to be about 10-30 individ. m^<-3>. This is approximately half of the maximum densities previously reported in inshore open waters. Vertically, the maximum abundance was observed at a depth of 2 m beneath the undersurface of the ice. The size ranged 15.40-27.05 mm in body length, and most P. elegans were adult forms of Stage II in ovary maturity. These findings suggest that in the boreal waters P. elegans occurs commonly under the sea ice, and that the maturing adult forms appear in proximity of the ice even in the daytime. departmental bulletin paper